Polynoe Savigny [sic], 1818 (Annelida Polychaeta): type species designated under the plenary powers - International Commission on Zoological Nomenclature [ICZN] (Bulletin of Zoological Nomenclature, 1984)
None. Begins: ""RULING. - (I) Under the plenary powers, all designations hitherto made for the nominal genus Polynoe Savigny [sic], 1818, are hereby set aside, and the nominal species Polynoe scolopendrina Savigny, 1812 [sic], is designated as type species of that genus. (2) The generic name Polynoe Savigny [sic], 1818 (gender: feminine), type species, by designation under the plenary powers in (I) above, Polynoe scolopendrina Savigny, 1822, is hereby placed on the Official List of Generic Names in Zoology with the Name Number 2208."
World Polychaeta Database (WPolyDb). Lamarck is the 1818 author of Polynoe, not Savigny